2008
DOI: 10.1529/biophysj.108.132928
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-Specific Conformational Flexibility of SNARE Transmembrane Helices Probed by Hydrogen/Deuterium Exchange

Abstract: SNARE proteins mediate fusion of intracellular eukaryotic membranes and their alpha-helical transmembrane domains are known to contribute to lipid bilayer mixing. Synthetic transmembrane domain peptides were previously shown to mimic the function of SNARE proteins in that they trigger liposome fusion in a sequence-specific fashion. Here, we performed a detailed investigation of the conformational dynamics of the transmembrane helices of the presynaptic SNAREs synaptobrevin II and syntaxin 1a. To this end, we r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
76
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 49 publications
(79 citation statements)
references
References 57 publications
3
76
0
Order By: Relevance
“…Nonpolar ␤-branched residues (valine and isoleucine) are traditionally thought of as being disruptive of ␣-helical structures; however, studies of synthetic peptides in detergent micelles demonstrated that these residues are incorporated into hydrophobic ␣-helices as easily as leucine (39,40). Additionally, as ␤-branched residues are thought to add conformational plasticity to membrane ␣-helices (33,54,72), these residues could be important for driving lipid disordering and later steps of membrane fusion. Thus, inclusion of these residues within viral TMDs may both facilitate promotion of ␣-helical structure and impart a degree of structural flexibility which alanine or residues of similar ␣-helical propensity could not.…”
Section: Discussionmentioning
confidence: 99%
“…Nonpolar ␤-branched residues (valine and isoleucine) are traditionally thought of as being disruptive of ␣-helical structures; however, studies of synthetic peptides in detergent micelles demonstrated that these residues are incorporated into hydrophobic ␣-helices as easily as leucine (39,40). Additionally, as ␤-branched residues are thought to add conformational plasticity to membrane ␣-helices (33,54,72), these residues could be important for driving lipid disordering and later steps of membrane fusion. Thus, inclusion of these residues within viral TMDs may both facilitate promotion of ␣-helical structure and impart a degree of structural flexibility which alanine or residues of similar ␣-helical propensity could not.…”
Section: Discussionmentioning
confidence: 99%
“…Mass spectrometry (MS) is increasingly being used for various types of IMP studies [1,[17][18][19][20][21][22][23][24][25][26][27][28]. Covalent labeling coupled with MS [29] can provide structural information on IMPs.…”
mentioning
confidence: 99%
“…1 TMDs that were designed to contain Val and Leu at different ratios. 3 Higher membrane fusogenicity correlates with enhanced backbones dynamics, that is with the extent of local and transient helix unfolding, 4,5 which is in accord with the known helix-destabilizing role of b-branched residues.…”
Section: Introductionmentioning
confidence: 63%
“…The advantage of recording DHX kinetics in isotropic solution is that all amide hydrogen atoms are accessible to solvent while a membrane shields part of a transmembrane peptide from exchange. 4,5 Circular dichroism (CD) spectroscopy revealed the characteristic line shapes diagnostic of a-helices with minima at 208 and 222 nm. Quantitative evaluation of the spectra indicates a-helix contents $70% [ Fig.…”
Section: Resultsmentioning
confidence: 99%